Analysis of the Characteristics of Pregnancy and Delivery before and after Implementation of the Two-child Policy - Zhang, Hong-Xia; Zhao, Yang-Yu; Wang, Yong-Qing (Chinese medical journal, 2018)
Background： After the two-child policy is frilly implemented, new challenges regarding pregnancy management and the treatment of pregnancy complications will arise. The aim of this study was to analyze the characteristics of pregnancy and delivery before and after the implementation of the two-child policy to make suggestions on the quality assurance of the new era of obstetrics. Methods： In total, 5895 cases of pregnant women who delivered from April 2016 to March 2017 in Peking University Third Hospital served as the study group and 5103 cases of pregnant women who delivered from January to December 2015 served as the control group. The characteristics of pregnancy and delivery were retrospectively analyzed. Results： In the study group, the percentage of pregnant women who were older （over 40 years） （3.6% vs. 2.2%）, were multipara （30.3% vs. 17.0%）, received irregular prenatal care （ 1.5% vs. 0.9%）, were transferred for treatment from a subordinate hospital （4.4% vs. 2.8%）, and were not residents of Beijing （3.8% vs. 2.2%）, were significantly increased compared with the control group （P 〈 0.05）. In the study group, the rate of a hypertensive disorder complicating pregnancy （6.4% vs. 5.0%）, gestational diabetes mellitus （25.3% vs. 23.1%）, dangerous placenta previa （3.0% vs. 2.3%）, placental implantation （2.4% vs. 1.8%）, and severe postpartum hemorrhage （2.8% vs. 1.9%） was significantly increased compared with the control group （P 〈 0.05）. In the study group, the cesarean section rate during primipara was significantly reduced compared with the control group （42.0% vs. 44.2%）. However, the rate during inultipara was significantly increased compared with the control group （P 〈 0.05）. Indications for cesarean section in the study group as well as the percentages of scared uterus and placenta previa were significantly increased compared with the control group （P 〈 0.05）. Conclusions： According to the current situation, better methods are needed to strengthen pregnancy and delivery management, reduce the rate of cesarean section, and ensure a positive outcome for mothers and babies.